"God Didn't Make a Mistake in Creating Me": Intrapersonal Resilience Processes among Gay and Bisexual Male Youth in Kenya - Gary W. Harper; Katherine A. Lewis; Gabriella A. Norwitz; Elijah Ochieng Odhiambo; Laura Jadwin-Cakmak; Felix Okutah; Kendall Lauber; Teddy Aloo; Ben Collins; Edwin Gumbe; K Rivet Amico; Kennedy Olango; et al. (MDPI AG, 2021)
Gay and bisexual male youth in Kenya experience human rights violations, including pervasive stigma and discrimination, and these oppressive forces are associated with elevated rates of mental health concerns. Despite these challenges, many gay and bisexual male youth in Kenya are thriving during this critical developmental period. This study explored intrapersonal processes that gay and bisexual male youth in Kisumu, Kenya, highlight as important to developing, and demonstrating resilience in the face of adversity. We conducted qualitative in-depth interviews (IDIs) with 40 gay and bisexual male youth, ages 20-30 (mean = 26.4), and an additional 20 IDIs with gay and bisexual men, ages 22-45 (mean = 26.6), who were working as peer educators (total n = 60), all in Kisumu, Kenya. A total of nine primary themes emerged which describe various intrapersonal resilience processes enacted by gay and bisexual male youth, including sexual identity acceptance, self-confidence, self-love, religious/spiritual affirmation, adaptive coping, successful navigation, legal rights awareness, economic stability, and advocacy satisfaction. These data demonstrate the range of positive personal processes that promote mental health and wellbeing among gay and bisexual male youth in Kenya. We discuss implications of these findings for community-based interventions, and call for a research paradigm shift away from deficits and toward resilience.